Association between TP73 G4C14-A4T14 polymorphism and different cancer types: an updated meta-analysis of 55 case–control studies. Issue 10 (October 2022) - Jafrin, Sarah; Aziz, Md. Abdul; Islam, Mohammad Safiqul
Objective: The TP73 G4C14-A4T14 variant has been associated with elevated cancer risk, but the evidence is inconclusive. We performed a meta-analysis to clarify the role of this variant in cancer development. Methods: Eligible literature was selected by searching PubMed, Google Scholar, Cochrane Library, and Embase. The meta-analysis was performed using Review Manager 5.4. Results: A meta-analysis of 55 case–control studies showed that the G4C14-A4T14 variant was significantly associated with overall cancer development in five genetic models, including the allele model (AM), codominant model 1 (COD1), COD2, dominant model (DM), and over-dominant model (OD). Sub-group analysis based on ethnicity showed significantly higher risks in Africans in COD2 and RM and in Whites in AM, COD2, DM, and recessive model (RM). Cancer-specific subgroup analysis identified significant risks of gynecological (ovarian, cervical, and endometrial cancer), colorectal, oral, head and neck, and other cancers. Moreover, hospital-based controls revealed significant cancer risks in the AM, COD1, COD2, DM, and RM genetic models. Our findings were confirmed by trial sequential analysis. Conclusion: This meta-analysis confirmed that TP73 G4C14-A4T14 significantly elevates the overall cancer risk, especially in White, African, and hospital-based populations, and specifically predisposes individuals to gynecological, colorectal, oral, and head and neck cancers. This meta-analysis was registered at INPLASY (registration number: INPLASY202210070).